Application of Artificial Intelligence in Contemporary Business: An Analysis for Content Management System Optimization - Mandapuram, Mounika (Asian Business Review, 2017)
Modern business is vital to finance, and AI has revolutionized the modern industry. Automation of many business operations has raised global concerns and alarms. Current business and related jobs are rising dramatically as the global population grows. Business administrators’ conventional methods could be more efficient for these needs. These new tactics properly manage business products and services so industry persons may use technology to boost profits. It has protected harvest yield from environmental changes, overpopulation, changing business demands, and food safety challenges. Artificial intelligence can promote intelligent production methods to reduce loss and increase returns. Using artificial intelligence platforms, one can collect a considerable amount of data from government and public sites or real-time monitoring and collection of different data using IoT (Internet of Things) and then use it to empower business people to solve all their business problems. This research helps business people worldwide improve their business techniques. This paper uses the waterfall technique to develop and build an intelligent system by sequentially collecting data, analyzing requirements, planning, coding, testing, and implementing. This system can also generate ideas for managing common challenges in farm information systems, improving policy programs, augmentation and analysis, and managing production data. Finally, management information systems are analyzed, and suggestions for further development are made.